Estimativa de modelo de velocidade em profundidade a partir de velocidades de migração em tempo - VALENTE, Leandro da Silva Sadala (2019)
One of the major challenges to seismic imaging in complex geological regions is velocity model building in depth. If lateral variation in the propagation velocity is moderate, a depth velocity model can be build starting from time migration velocities. I review the theoretical relation between these velocities using the paraxial ray theory. The estimation of depth velocities from time migration velocities is unstable. I implement regularized versions of the time to depth conversion based on Dijkstra-like fast marching methods. Two more e cient variations from the original algorithm proposed recently in the literature are evaluated. The relation between the polynomial degree and the regularization value for the least-squares problem associated with the wavefront interpolation are determined. Finally, I test these algorithms on 2D synthetic data and compare the results obtained by three ray tracing algorithms.